Novel Research in Low-Dimensional Systems - Ciftja, Orion (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The application of novel experimental tools in many scientific fields has created an urgent need for an improved understanding of many new physical phenomena that emerge under such conditions. In particular, phenomena that occur in low-dimensional systems have drawn the interest of many experimental and theoretical groups globally. The aim of this reprint is to provide an overview of the current research in low-dimensional systems by attracting contributions from a number of specialists in the field. This way, we attempt to provide important insights on the large variety of scientifically fascinating and technologically important phenomena that are currently being investigated. The covered topics include original research articles on the fundamental principles and experimental aspects that apply to various low-dimensional systems, such as quantum dots, graphene systems, ultrathin films, superconducting films, novel nanoscale devices, etc. This reprint includes research papers from both theoretical and experimental groups. Many phenomena are studied from a multi-disciplinary perspective in such a way as to explore key important developments in the field.